Cooking Class Learning to Improve Children's Fine Motor Skills - Indria, Anita; Masniati, Dona; Pasaleron, Roni (Journal of Islamic Early Childhood Education, 2025)
Fine motor development is one of the important aspects of early childhood growth and development, as it plays a major role in learning readiness and independence. This study aims to examine the implementation of cooking class activities in improving fine motor skills of early childhood students in preschool. The research employed a qualitative approach with a case study design. The research subjects consisted of teachers, the school principal, and students. Data were collected through observation, interviews, and documentation, and then analyzed using a descriptive qualitative method. The results of the study show that cooking class activities make a positive contribution to improving children’s fine motor skills, particularly through activities such as stirring, pouring, molding, and decorating food. In addition, this activity also has an impact on the development of other aspects, such as increased self-confidence, independence, cooperation, and concentration. The findings indicate that the cooking class is an effective, enjoyable, and holistic learning method that supports optimal early childhood development and can serve as an innovative learning activity in early childhood education institutions.